Effect of supplementary feeds with different protein levels on growth and production of Indian butter catfish Ompok bimaculatus (Bloch, 1794) in fertilised ponds - Debnath, Chandan; Sahoo, Lopamudra; Debnath, Biswajit; Yadav, Gulab Singh; Datta, M. (Indian Journal of Fisheries, 2018)
The study evaluated the effect of supplementary feeds with varying protein levels on the growth and production of Ompok bimaculatus (Bloch, 1794) in earthen ponds. The stocking density was 4000 fingerlings ha-1 and culture period was 6 months. Feed-1 comprised rice bran and mustard oil cake at 1:1 ratio, whereas, Feed-2 and Feed-3 additionally contained fish meal, wheat flour and vitamin-mineral premix. The crude protein content was estimated as 18.84% in Feed-1, 30.47% in Feed-2 and 35.24% in Feed-3. The water quality parameters and plankton composition were assessed monthly and soil quality was assessed at the beginning and end of the culture period. All parameters were within the ideal limits for pond farming. Fish growth parameters were assessed monthly. The final weight (p≤0.05) and survival (p≥0.05) with Feed-2 and Feed-3 were higher than that obtained with Feed-1. Feed conversion ratio (FCR) for Feed-2 and Feed-3 were better as compared to Feed-1. Fish production was 10% more with Feed-2 and 13% more with Feed-3. Benefit costcratio (BCR) was highest with Feed-2. Carcass composition among the treatments showed trivial variation (p≥0.05). From the results of the study, it can be concluded that 30% dietary protein is ideal for sustainable farming of O. bimaculatus in fertilised pond systems.